Aerobic training prevents cardiometabolic changes triggered by myocardial infarction in ovariectomized rats. Issue 2 (7th July 2020) - Ruberti, Olívia Moraes; Sousa, Andressa Silva; Viana, Laís Rosa; Pereira Gomes, Moisés Felipe; Medeiros, Alessandra; Gomes Marcondes, Maria Cristina Cintra; Borges, Luciano de Figueiredo; Crestani, Carlos Cesar; Mostarda, Cristiano; Moraes, Telma Fátima da Cunha; Canevarolo, Rafael Renatino; Delbin, Maria Andreia; et al.
Abstract: This study aimed to evaluate the impact of aerobic training (AT) on autonomic, cardiometabolic, ubiquitin‐proteasome activity, and inflammatory changes evoked by myocardial infarction (MI) in ovariectomized rats. Female Wistar rats were ovariectomized and divided into four groups: sedentary + sham (SS), sedentary + MI (SI), AT + sham surgery (TS), AT + MI (TI). AT was performed on a treadmill for 8 weeks before MI. Infarcted rats previously subjected to AT presented improved physical capacity, increased interleukin‐10, and decreased pro‐inflammatory cytokines. Metabolomic analysis identified and quantified 62 metabolites, 9 were considered significant by the Vip Score. SS, SI, and TS groups presented distinct metabolic profiles; however, TI could not be distinguished from the SS group. MI dramatically increased levels of dimethylamine, and AT prevented this response. Our findings suggest that AT may be useful in preventing the negative changes in functional, inflammatory, and metabolic parameters related to MI in ovariectomized rats. Abstract : Aerobic exercise training, performed before MI, in ovariectomized rats. Improved physical capacity, baroreflex sensitivity, cardiovascular autonomic control, and cardiac proteasome activity. Attenuated cardiac inflammatory response and metabolic changes caused by myocardial ischemia.